Development of Students’ Project Thinking: A comparative Analysis of Technology-mediated and Conventional Education (Journal of Educational Sciences, 2026)
This study examines the impact of technological platforms (Duolingo, Coursera, Quizlet) on the development of project thinking, cognitive skills, memorization, problem-solving, creativity, and engagement. A survey was conducted among 77 students majoring in “Pedagogy and Psychology” to analyze their understanding of the strengths of digital platforms, compare learning outcomes, and identify barriers to the implementation of digital education. Three hypotheses were tested: (1) Digital tools and teaching methods outperform conventional approaches in memorization efficiency and visual/creative thinking but are inferior in deep problem-solving and long-term knowledge retention; (2) Gamified platforms (e.g., Kahoot) enhance student engagement while both contributing to and helping manage distractions; (3) Digital tools (Coursera, Canva) are superior to conventional methods in structured task performance (e.g., following project templates), whereas conventional methods are more applicable for adaptive decision-making in unpredictable scenarios. The results confirmed that platforms such as Quizlet and Canva improve students’ memorization and creativity, while conventional instruction is preferable for complex problem-solving and teamwork; gamified tools correlate with higher motivation but also a greater number of distractions.Keywords: project-based thinking, educational psychologists, technologies, digital tools, education, cognitive skills.